Case Report: CT manifestations of acute portal vein thrombosis: cases report and literature review - Zhou, Lin; Huang, Zhi-cheng; Lin, Xiao-hui; Zhang, Shao-jin; He, Ya (Frontiers in Radiology, 2025)
Acute portal vein thrombosis (APVT) is a rare condition characterized by recent thrombus formation within the main portal vein or its branches. APVT occurring in patients without underlying cirrhosis or malignancy represents an even rarer presentation, with an estimated prevalence of 0.7–3.7 per 100,000 individuals. However, it can lead to severe complications, including intestinal infarction and mortality. We report two cases presenting with abdominal pain without an apparent precipitating factor. Both patients were diagnosed with APVT based on contrast-enhanced computed tomography (CT) findings, clinical presentation, and laboratory parameters. Depending on the extent of portal vein occlusion, distinct therapeutic approaches were employed: one patient underwent interventional therapy combining transjugular mechanical thrombectomy/thrombolysis with transjugular intrahepatic portosystemic shunt (TIPS) placement, while the other received systemic pharmacological thrombolysis. Successful portal vein recanalization was achieved in both patients, who subsequently recovered and were discharged. These cases underscore that prompt diagnosis and management of APVT can avert adverse clinical outcomes. Contrast-enhanced CT demonstrates significant value in classifying APVT, assessing disease severity, evaluating treatment response, and identifying complications, thereby providing crucial evidence for clinical decision-making.